2017
DOI: 10.1186/s12905-017-0407-x
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of cervical and breast cancer stigma in Karnataka, India

Abstract: BackgroundBreast and cervical cancer are two of the most common cancers among women worldwide and were the two leading causes of cancer related death for women in India in 2013. While it is recognized that psychosocial and cultural factors influence access to education, prevention, screening and treatment, the role of stigma related to these two cancers has received limited attention.MethodsTwo qualitative exploratory studies. One focusing on cervical cancer, the other on breast cancer, were conducted in Karna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
111
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(126 citation statements)
references
References 50 publications
10
111
2
3
Order By: Relevance
“…Other studies have also described similar manifestations of stigmatization. The physical or social isolation and verbal abusive comments had also been described in a study in Karnataka, India [15], and in a study on cervical cancer stigma in rural Kenya [25].…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Other studies have also described similar manifestations of stigmatization. The physical or social isolation and verbal abusive comments had also been described in a study in Karnataka, India [15], and in a study on cervical cancer stigma in rural Kenya [25].…”
Section: Discussionmentioning
confidence: 86%
“…Our study revealed that pertaining cervical cancer to ultimate death and fear of transmission assuming it as a communicable disease are the driving factors for the origin of stigma. Similar perceptions, cancer as a communicable disease and leads to ultimate death, driving the stigmas related to cervical cancer are also described on a qualitative study of stigma related to cervical and breast cancer in Karnataka, India [15] and a study on stigma related to cervical cancer among women in Brazil [21]. Furthermore, the mind of the people being so constantly preoccupied with the thoughts and ideas of blaming or attributing cervical cancer to the individual’s promiscuous sexual behavior, like sleeping with multiple men, or relating it to sexually transmitted disease [21] or blaming cervical cancer as a punishment to individual’s bad deeds/transgressions, like assuming they must have done something wrong [15], it naturally rooted the stigma related to cervical cancer.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations